On One Publication by Tamar Papava (“Georgian Woman in Our Chronicle”) in the Newspaper “Kartuli Azri” - Kutivadze, Nestan ("Intercultural Dialogues" Transactions, 2023)
One of the prominent representatives of the Georgian emigration of the 20th century is the writer and publicist Tamar Gogolashvili-Papava. She lived with her husband Akaki Papava first in Germany and Austria, and later from 1949 in South America, Argentina. However, through all their activities and consciousness, Tamar and Akaki Papava were connected with Georgia and the Georgian affairs, which can be clearly confirmed by their artistic-publicistic and scientific legacy being very diverse from a creative point of view. From the 1910s-1920s, Tamar Papava fruitfully collaborated with the magazines and newspapers published in Georgia. Later she published noteworthy letters in emigration periodicals printed abroad. Today, it can be safely said that Tamar Papava's publicism plays an important part of the Georgian emigrant cultural heritage, in which many dramatic pages of our history and her own tempestuous contemporary life, the first half of the 20th century, are reflected. In 1966-1967, in the Georgian emigrant newspaper “Kartuli Azri” (Georgian Opinion) printed in New York, Tamar Papava published the letter "Georgian Woman in Our Chronicle" with continuations. The author's goal is clear from the title. She aims to present the role of Georgian women in the history of Georgia. In this regard, she thoroughly studies the information preserved in "Life of Kartli". As the publicist notes, she only reviews the data that the history "preserved by chance". Despite this, the outstanding contribution of a Georgian woman to her homeland can clearly be seen. These contributions are equally made by the women both from noble and lower social classes, and include such issues as: professing and defending the faith, the upbringing of kings, the tradition of entrusting the children to wet nurses, as well as women’s dedication to the unification of the country and the fight against Russia. However, the reception of the role of Georgian women towards their own country is not limited to the aforementioned issues. Emphasizing the efforts made by women at different stages of our history is one of the main directions of Tamar Papava's publicism, which can clearly be confirmed by the mentioned letter.